IMPOSITION OF NATURE AGAINST MATERIAL LAW UNDER JUDGE VERDICT OF CYBERPORN CASE IN EAST JAVA - Hwiian Christianto (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Cyberporn case has become a challenge for the Judge in East Java jurisdiction to fulfill legal provisions and uphold the law in the society. The problem appears on the meaning of nature against the material law itself under judge’s consideration and the measurement used to determine that a judge has imposed nature against the material law. In order to decrease the problem, research method of socio-legal is used to analyze the basic law of imposition of nature against material law associated with the use of nature against the material law by a judge in examining and deciding a case. The result of the research shows that judge considers nature against the material law in giving a verdict for cyberporn case. Judge’s consideration of norms of morality is based on religious aspect, culture and the development of people’s condition. Judge’s verdict also includes socio-juridical which is automatically accepted by the society.Keywords: nature against material law, judge, cyberporn